(3x+2)+(2x^2+3x-1)
Please answer ty:)
1 answer:
Answer = 2x^2+6x+1
3x+2+2x^2+3x-1
3x+1+2x^2+3x
Now combine like terms
3x+1+2x^2+3x
6x+1+2x^2
Rearrange terms
6x+1+2x^2
2x^2+6x+1
You might be interested in
<span>4x – 20 = 900
4x = 900+20
4x = 920
x = 920/4
x = 230
he earned $230
</span>
I don’t even know what to say.
Answer:
![8d](https://tex.z-dn.net/?f=8d)
Step-by-step explanation:
![6d + 2d = 8d](https://tex.z-dn.net/?f=%206d%20%2B%202d%20%3D%208d)
32 is your initial value, because that is what he starts with
Answer:
D. X= -100
Step-by-step explanation:
5×x/5=5×(-20) (reduce and multiply)
X= -100